2012
DOI: 10.1055/s-0032-1330387
|View full text |Cite
|
Sign up to set email alerts
|

Early Response to Anti-Tumoral Treatment in Hepatocellular Carcinoma - Can Quantitative Contrast-Enhanced Ultrasound Predict Outcome?

Abstract: Quantitative CEUS reveals variations of dynamic parameters of blood flow during anti-tumoral therapy in liver cancer patients. Further investigations and clinical trails have to confirm that the TTP is a promising parameter in the prediction of early response to sorafenib-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Tissue perfusion may be quantified also by further evaluating the replenishment kinetics of the volume of microbubbles after their destruction in the imaged slice (using high mechanical index US), obtaining quantitative parameters related to local tissue perfusion [15, 19]. However, we believe that the first step, as already performed for other organs and in our previous study [34], is the qualitative and semiquantitative analysis; time-intensity curves providing quantitative data require very large cohorts of patients in order to achieve a statistical relevance, so we feel that a quantitative analysis would be of little value in this study [28, 29, 32, 33]. …”
Section: Discussionmentioning
confidence: 96%
“…Tissue perfusion may be quantified also by further evaluating the replenishment kinetics of the volume of microbubbles after their destruction in the imaged slice (using high mechanical index US), obtaining quantitative parameters related to local tissue perfusion [15, 19]. However, we believe that the first step, as already performed for other organs and in our previous study [34], is the qualitative and semiquantitative analysis; time-intensity curves providing quantitative data require very large cohorts of patients in order to achieve a statistical relevance, so we feel that a quantitative analysis would be of little value in this study [28, 29, 32, 33]. …”
Section: Discussionmentioning
confidence: 96%
“…However, TTP pre and TTP in were found to have no significant difference regarding the CR or PR lymph node response status. In a study by Knieling et al (22), hepatocellular carcinoma patients were treated with sorafenib and the TTP increased as early as 1 month after the initiation of the treatment in the responder group compared to the non-responder group. In the study by Schirin-Sokhan et al (23), non-primary resectable liver metastases from colorectal cancer were treated with bevacizumab-based chemotherapy and it was demonstrated that the baseline TTP was significantly lower in the responder group compared to the non-responders, suggesting that low baseline TTP significantly correlates with tumor response according to RECIST.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue perfusion may be quantified also by further evaluating the replenishment kinetics of the volume of microbubbles after their destruction in the imaged slice (using high mechanical index US), obtaining quantitative parameters related to local tissue perfusion [15,19]. However, we believe that the first step, as already performed for other organs and in our previous study [34], is the qualitative and semiquantitative analysis; timeintensity curves providing quantitative data require very large cohorts of patients in order to achieve a statistical relevance, so we feel that a quantitative analysis would be of little value in this study [28,29,32,33].…”
Section: Discussionmentioning
confidence: 91%
“…Comparison with other imaging modalities (such as MRI imaging T1 weighted GD) will be necessary for defining further advantages or limitations of this technique when compared with other imaging standards in actual practice. Moreover, further studies aimed at quantitative data analysis are mandatory for a rigorous validation of the method: these results will further improve CEUS characterization of cerebral gliomas and will also enhance knowledge of tumor biology, possibly leading to prediction of the responsiveness to therapy of a specific individual tumor, or to orientation during the choice of the best therapeutic option [32,33].…”
Section: Discussionmentioning
confidence: 99%